The Effect of Distributed Leadership, School Climate, and Work Motivation on Teacher’s Job Satisfaction at Senior High School - Istiqomah, Istiqomah; Karnati, Neti; Rugaiyah, Rugaiyah (Journal of Posthumanism, 2025)
Objective: This study aims to test and analyze the influence of distributed leadership, school climate, and work motivation on teacher’s job satisfaction at senior high school in Jakarta. Theoretical Framework: In this topic focus on the meaning [Teachers Job Satisfaction, Distributed Leadedrship,School Climate,Work Motivation]. Method: Quantitative method with survey approach was used involving 370 teachers as respondents. Data collection technique was done through questionnaires arranged based on indicators of each variable. The data obtained were analyzed statistically Results and Discussion: The results showed: First, distributed leadership significantly impacts teacher job satisfaction, accounting for 60.2% of the variance, indicating a fairly strong influence. Second, school climate demonstrates an even greater impact, with a very strong influence of 78.4% on teacher job satisfaction, emphasizing its critical role in fostering a positive and satisfying work environment. Third, work motivation contributes to teacher job satisfaction at a moderate level, influencing 35.1% of the outcome. These findings highlight the varying degrees of importance of leadership, school climate, and motivation in shaping teacher satisfaction levels. Research Implications: The findings of this study serve as a basis for schools in developing strong distributed leadership as a supporter in meeting teacher job satisfaction. This study contributes to the development of theories in the fields of educational management and organizational psychology. Originality/Value: The results of the study can strengthen existing theories on how distributed leadership, school climate, and motivation affect teacher job satisfaction.